2007
DOI: 10.3892/ijo.31.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of the lymphatic marker podoplanin in diverse types of human cancer cells using a novel antibody

Abstract: Abstract. The mucin-type transmembrane glycoprotein podoplanin (also known as T1α, gp38 or Aggrus) is well established as one of the lymphatic-specific markers. Podoplanin was also reported to be associated with tumorinduced platelet aggregation and tumor metastasis. Here, we generated a novel monoclonal antibody (clone; 7B10) that specifically recognized human podoplanin, as assessed by enzyme-linked immunosorbent assay, Western blot analyses, immunohistochemistry and flow cytometry. 7B10 stained not only lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…D2-40 has been suggested as a marker of cancer stem cells in squamous-cell carcinomas 40. To the best of our knowledge, expression of this protein had been previously reported in colorectal cancer-derived cells only in one study 41. The small number of positive cases which we found herein did not allow us to draw any conclusions on the possible significance of D2-40 expression in colorectal carcinoma.…”
Section: Discussioncontrasting
confidence: 75%
“…D2-40 has been suggested as a marker of cancer stem cells in squamous-cell carcinomas 40. To the best of our knowledge, expression of this protein had been previously reported in colorectal cancer-derived cells only in one study 41. The small number of positive cases which we found herein did not allow us to draw any conclusions on the possible significance of D2-40 expression in colorectal carcinoma.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, PDPN is expressed on numerous cell types other than LECs to which bloodborne platelets would not normally be exposed, including pulmonary epithelial cells, 39 mesothelial cells, 40 glomerular podocytes, 39,41 and numerous types of tumor cells. 42 It is therefore possible that PDPN-CLEC-2 interaction may mediate a novel mechanism for extravascular platelet activation that functions during hemostasis after trauma. The ability of PDPN to activate platelets through CLEC-2 receptors has also been proposed as a mechanism by which tumor cells may activate platelets to regulate tumor growth and metastasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Podoplanin has been used as a specific marker for lymphatic vessels, and its upregulation has been observed in several cancers (14)(15)(16)(17)(18). It has been reported that podoplanin is expressed in ∼90% of OSCCs and is restricted to the invasive front of squamous cell carcinoma (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Podoplanin deficiency in mice results in congenital lymphedema (13), and podoplanin expression has been reported in squamous cell carcinomas of esophagus, lung, skin, and oral cavity (14)(15)(16)(17)(18). Podoplanin is also expressed in hyperplastic and dysplastic areas adjacent to the primary tumors (17,18), indicating that its abnormal expression occurs early in oral tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%